Time to Surgery Following Short-Course Radiotherapy in Rectal Cancer and its Impact on Postoperative Outcomes. A Population-Based Study Across the English National Health Service, 2009–2014. Issue 2 (February 2020) - Levick, B.A.; Gilbert, A.J.; Spencer, K.L.; Downing, A.; Taylor, J.C.; Finan, P.J.; Sebag-Montefiore, D.J.; Morris, E.J.A.
Abstract: Aims: Preoperative short-course radiotherapy (SCRT) is an important treatment option for rectal cancer. The length of time between completing SCRT and surgery may influence postoperative outcomes, but the evidence available to determine the optimal interval is limited and often conflicting. Materials and methods: Information was extracted from a colorectal cancer data repository (CORECT-R) on all surgically treated rectal cancer patients who received SCRT in the English National Health Service between April 2009 and December 2014. The time from radiotherapy to surgery was described across the population. Thirty-day postoperative mortality, returns to theatre, length of stay and 1-year survival were investigated in relation to the interval between radiotherapy and surgery. Results: Within the cohort of 3469 patients, the time to surgery was 0–7 days for 76% of patients, 8–14 days for 19% of patients and 15–27 days for 5% of patients. There was a clear variation in relation to different patient characteristics. There was, however, no evidence of differences in postoperative outcomes in relation to interval length. Conclusions: This study suggests that the time interval between SCRT and surgery does not influence postoperative outcomes up to a year after surgery. The study provides population-level, real-world evidence to complement that from clinical trials. Highlights: The optimal interval between SCRT and rectal surgery is not known. SCRT and surgery intervals vary substantially across the English NHS. There are no differences in surgical outcomes with intervals of up to 27 days after SCRT.